Comparative analysis of AES algorithms and implementation of AES in Arduino - Ismat, Tanzir (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.